APPLICATION OF THE PRINCIPLE OF JUSTICE IN NON-ADJUDICATIVE SETTLEMENT OF BANKING DISPUTES FROM THE PERSPECTIVE OF ISLAMIC LAW - Maskanah, Ummi; Md Nor, Mohd Zakhiri; Mulyana, Aji (Fakultas Syariah, 2024)
Improving Indonesia's economy is crucial for overcoming poverty, especially post-Covid-19, which caused many business closures. The government introduced the People's Business Credit (KUR) programme to support MSMEs, though some programmes face bad debt issues. In West Bandung Regency, MSMEs use the programme extensively for economic recovery. This research examines whether the Non-Adjudication Settlement model between MSME actors and Islamic banks upholds principles of justice. Using normative and empirical juridical methods, the study incorporates primary, secondary, and tertiary legal materials, along with interviews with MSME actors and KUR-issuing banks. Dispute resolution for problem credits can occur through adjudication (court) or non-adjudication (out-of-court). Islamic banks integrate values from Islamic teachings, encompassing law, morality, and social procedures. For KUR bad credit disputes, Islamic banks are mandated to select processes aligning with Islamic values of truth, justice, and compassion. The non-litigation settlement model is found to reflect Islamic and Indonesian societal values, emphasizing deliberation for consensus and justice. The contribution of this research is to provide an understanding of the effectiveness of the non-adjudication settlement model in handling bad credit in the KUR program, aligning with Islamic values and reflecting Indonesian values. This model can serve as a fairer and more efficient dispute resolution alternative for MSMEs and Islamic banks in Indonesia. Meningkatkan ekonomi Indonesia menjadi sangat penting untuk mengatasi kemiskinan, terutama pasca-Covid-19 yang menyebabkan banyak bisnis tutup. Pemerintah memperkenalkan program Kredit Usaha Rakyat (KUR) untuk mendukung UMKM, meskipun beberapa program menghadapi masalah kredit macet. Di Kabupaten Bandung Barat, UMKM menggunakan program ini secara luas untuk pemulihan ekonomi. Penelitian ini mengkaji apakah model Penyelesaian Non-Adjudikasi antara pelaku UMKM dan bank syariah menjunjung prinsip-prinsip keadilan. Dengan menggunakan metode yuridis normatif dan empiris, studi ini melibatkan bahan hukum primer, sekunder, dan tersier, serta wawancara dengan pelaku UMKM dan bank penerbit KUR. Penyelesaian sengketa untuk kredit bermasalah dapat dilakukan melalui adjudikasi (pengadilan) atau non-adjudikasi (di luar pengadilan). Bank syariah mengintegrasikan nilai-nilai dari ajaran Islam, yang mencakup hukum, moralitas, dan prosedur sosial. Untuk sengketa kredit macet KUR, bank syariah diwajibkan memilih proses yang sesuai dengan nilai-nilai Islam tentang kebenaran, keadilan, dan kasih sayang. Model penyelesaian non-litigasi ditemukan mencerminkan nilai-nilai Islam dan nilai-nilai masyarakat Indonesia, menekankan musyawarah untuk mufakat dan prinsip keadilan. Kontribusi penelitian ini adalah memberikan pemahaman tentang efektivitas model penyelesaian non-adjudikasi dalam menangani kredit macet dalam program KUR, yang sesuai dengan nilai-nilai Islam dan mencerminkan nilai-nilai Indonesia. Model ini dapat menjadi alternatif penyelesaian sengketa yang lebih adil dan efisien bagi pelaku UMKM dan bank syariah di Indonesia.